Word-Formation of Sundanese Food Names on Instagram Hashtag: A Morphological Study - L.M Ady Marlan Wardoyo Hasim; Lia Maulia Indrayani; Ypsi Soeria Soemantri (Celt: A Journal of Culture, English Language Teaching & Literature, 2021)
Abstract: Sundanese cuisine names are popular in everyday social interactions as well as social media, with Instagram being one of them. The purposes of this study are to determine how words are formed and to look at the word-formation patterns that predominate in Instagram hashtags. All Sundanese food names used in this research are related to certain meals. This paper employs a qualitative method that deals with words, not numbers. The results show that blending is the most dominant type in the findings. It indicates that blending is mostly used by Instagram users in their posts.Key words: word formation, Sundanese food, morphological process